Role of nNOS in regulation of renal function in angiotensin II-induced hypertension - Cervenka, L; Kramer, H J; Malý, J; Heller, J (Hypertension (Dallas, Tex., 2001)
Previous studies have indicated that in normotensive rats, NO produced by neuronal NO synthase (nNOS) plays an important role in modulating tubuloglomerular feedback (TGF)-mediated afferent arteriolar constriction. It has also been shown that in angiotensin (Ang) II-infused hypertensive rats, there is a reduced ability of nNOS-derived NO to counteract this vasoconstriction. The present study was performed to (1) assess in vivo renal functional responses to intrarenal nNOS inhibition in control and Ang II-infused rats and (2) determine whether changes in renal function following nNOS inhibition are mediated by unopposed stimulation of Ang II receptor subtype 1 (AT(1)). Wistar rats were infused with either saline (SAL) or Ang II (80 ng/min) by osmotic minipumps implanted subcutaneously. Mean arterial blood pressure of SAL- and Ang II-infused rats on day 13 after implantation averaged 121+/-4 (n=28) and 151+/-5 (n=30), respectively (P<0.05). There were no differences in glomerular filtration rate (GFR) (0.68+/-0.09 versus 0.59+/-0.09 mL. min(-1). g(-1)), renal plasma flow (RPF) (2.66+/-0.31 versus 2.34+/-0.39 mL. min(-1). g(-1)), and absolute sodium excretion (0.37+/-0.07 versus 0.42+/-0.09 micromol. min(-1). g(-1)). Intrarenal infusion of SAL did not change GFR, RPF, and sodium excretion in either SAL-infused (n=7) or Ang II-infused rats (n=8). Acute intrarenal administration of the nNOS inhibitor S-methyl-L-thiocitrulline (L-SMTC; 0.3 mg/h) decreased GFR, RPF, and sodium excretion in SAL-infused rats (n=9) by 29+/-4%, 38+/-4%, and 70+/-4% compared with control values (P<0.05). The pretreatment by the AT(1) receptor antagonist candesartan (750 ng IR) in SAL-infused rats (n=7) effectively prevented the decrease in RPF (-3+/-3%) elicited by nNOS inhibition and resulted in an increase in GFR (+25+/-12, P<0.05) and a concomitant greater increase in sodium excretion (84+/-12%, P<0.05) compared with control values. In contrast, in Ang II-infused rats (n=10) intrarenal inhibition of nNOS by L-SMTC did not cause significant decreases in GFR, RPF and sodium excretion (-2+/-2%, -15+/-10%, and -14+/-10%, respectively). These results suggest that in normotensive rats nNOS-derived NO counteracts Ang II-mediated vasoconstriction in the pre- and postglomerular microcirculation. Furthermore, Ang II-infused rats exhibit an impaired ability to release NO by nNOS. Decreased nNOS activity is likely to account at least partially for the enhanced TGF responsiveness in Ang II-infused rats and thus may contribute to the maintenance of hypertension in this model.
Keywords: Animals; Benzimidazoles; Kidney; Thiourea; angiotensin II; Hypertension, Renal; Rats, Wistar; antagonisté receptorů pro angiotenzin; receptor angiotensinu typ 2; Natriuresis; Nitric Oxide Synthase Type I; Receptor, Angiotensin, Type 1; renální hypertenze; receptor angiotensinu typ 1; Glomerular Filtration Rate; benzimidazoly; Enzyme Inhibitors; Receptor, Angiotensin, Type 2; Nitric Oxide Synthase; Tetrazoles; thiomočovina; Citrulline; tetrazoly; krevní tlak; renální průtok plazmy; Renal Plasma Flow; Male; natriuréza; synthasa oxidu dusnatého, typ I; citrulin; inhibitory enzymů; synthasa oxidu dusnatého; bifenylové sloučeniny; krysa rodu Rattus; zvířata; mužské pohlaví; Angiotensin Receptor Antagonists; Biphenyl Compounds; Blood Pressure; ledviny; Rats; hodnoty glomerulární filtrace; Angiotensin II; potkani Wistar